2012
DOI: 10.1111/j.1744-313x.2012.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population genetic analysis of bovine MHC class II DRB3.2 locus in three Bos indicus cattle breeds of Southern India

Abstract: The present study was performed to evaluate the genetic polymorphism of BoLA-DRB3.2 locus in Malnad Gidda, Hallikar and Ongole South Indian Bos indicus cattle breeds, employing the PCR-RFLP technique. In Malnad Gidda population, 37 BoLA-DRB3.2 alleles were detected, including one novel allele DRB3*2503 (GenBank: HM031389) that was observed in the frequency of 1.87%. In Hallikar and Ongole populations, 29 and 21 BoLA-DRB3.2 alleles were identified, respectively. The frequencies of the most common BoLA-DRB3.2 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…However, scanty literature is available on the effect of experimental FMD infection on blood and serum profile of cattle, which is important for formulating the ameliorative measures to reduce the biotic stress on the animal due to the infection. In addition, an Indian native breed, Malnad Gidda, is believed to be tolerant of many infectious diseases including FMD; however, no systematic study has been carried out to establish the exactness of this perception [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, scanty literature is available on the effect of experimental FMD infection on blood and serum profile of cattle, which is important for formulating the ameliorative measures to reduce the biotic stress on the animal due to the infection. In addition, an Indian native breed, Malnad Gidda, is believed to be tolerant of many infectious diseases including FMD; however, no systematic study has been carried out to establish the exactness of this perception [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Lützelschwab et al 13 , Mycobacterium bovis co-infection does not influence the ability of cattle, either they carry or do not, to have the resistant allele in BoLA-DRB3 to bovine leukemia virus. Das et al 14 also documented a highly polymorphic BoLA-DRB3 on exon2 with significant breed-specific genetic diversities in three Bos indicus cattle breeds of South Indian hence recommended conservation to maintain native cattle genetic diversity. In Latin American Creole cattle breeds, Giovambattista et al 15 reported high genetic diversity of MHC DRB3 which could be as a result of multiple sources of germplasm and could be maintained by balancing selection.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of the review (Behl et al, 2012), among the breeds of species Bos taurus, 20 to 30 alleles are most often found. High allele diversity according to BoLA-DRB3 gene was determined for the Indian breed Malnad Gidda -37 variants (Das et al, 2012), Kalmyk cattle -36 variants, Russian Yaroslavl cattle (Sulimova, 2006) and Mongolian cattle (Ruzina et al, 2010) -35 variants in each, (Ruzina et al, 2010) and Iranian zebu-like Sistani cattle -32 variants (Mohammadi et al, 2009). The recent surveys of local and autochthonous breeds indicate that their allele polymorphism of the BoLA-DRB3 gene is broader than in the commercial and native ones.…”
Section: Discussionmentioning
confidence: 98%